The Influence of Hockey Table Games on Children's Physical Motor Skills Age 5-6 Years at Paud Rukun Bengkulu City - Aisyiah, Khofifah Nur; Nirwana, Evi Selva (International Journal of Education, Information Technology, and Others, 2024)
The problem at PAUD Rukun Bengkulu city is that children's physical motor skills are less developed, children are still not strong in holding toys, still not neat in arranging puzzles, children have not hit small tennis balls, children are still slow in moving, walking and jumping. The purpose of this study was to determine the effect of hockey table games on the physical motor skills of children aged 5-6 years at PAUD Rukun, Bengkulu city. The type of research used by the author is quasi-experimental design research, with data collection of observation sheets, anecdotal records and documentation. The results of the research that has been done, it can be concluded that there is an effect of hockey table games on the physical motor skills of children aged 5-6 years at PAUD Rukun Bengkulu city, this is evidenced by the increase in the average value of children who at the beginning of the study (pre-treatment) amounted to 39.71 to 44.92 after learning using hockey table games. The results of data analysis obtained the tcount value is 4.149 which is compared with the ttable (dk = 26 with the error rate set at 5%, which is 2.056), then tcount> ttable (4.149> 2.056).